Viral hepatitis in persons living with HIV in the post-COVID era - Soriano, Vicente; Moreno-Torres, Víctor; de Mendoza, Carmen; Corral, Octavio Jorge; Barreiro, Pablo (AIDS reviews, 2023)
Coinfection with hepatitis viruses A to E is frequent in persons living with HIV (PLWH) and causes significant morbidity and mortality. Oro-fecal transmissible hepatitis A and E mostly produce acute self-limited episodes in poor income regions and in non-vaccinated travelers. In high-income countries, outbreaks of hepatitis A occur in men having sex with men (MSM) and chronic hepatitis E is occasionally reported among PLWH with severe immunodeficiency. Chronic hepatitis B, C, and D are frequent in PLWH in highly endemic regions and globally in persons who inject drugs (PWID) and MSM. Progression to liver cirrhosis and development of hepatocellular carcinoma (HCC) is major clinical complications in coinfected patients. Current estimates for PLWH are of 38 million worldwide. Roughly 12% have chronic viral hepatitis (5 million). Coinfection figures are of 5-10% for HBV (2-4 million), 4% for HCV (1.5 million), and 15% of HBsAg+ for HDV (0.5 million). Oral direct-acting antivirals (DAA) cure almost all treated patients with hepatitis C. However, given that there is no protective HCV immunity, PLWH with high-risk behaviors may experience HCV reinfection episodes. Tenofovir is the drug of choice in PLWH with chronic hepatitis B, given its dual effect on HIV and HBV. Lifelong oral tenofovir suppresses HBV replication and ameliorate liver damage. However, the risk of HCC persists even in the absence of cirrhosis. Finally, HDV causes the worst of viral hepatitis with faster progression to cirrhosis and HCC. An entry inhibitor, bulevirtide, has recently been approved and another drug, lonafarnib, is completing Phase 3 trials. Combination antiviral therapy for hepatitis D could improve dramatically the poor prognosis of HIV-HDV coinfected patients. The resumption of good medical practices in PLWH after the big disruption caused by COVID-19 will reduce the burden of viral hepatitis coinfections. Renewed efforts on HAV and HBV vaccination of susceptible individuals and earlier and wider prescription of antiviral therapy for HBV, HCV, and/or HDV coinfection should be prioritized in PLWH. The benefits of innovative strategies for viral hepatitis, including pre-exposure prophylaxis or use of long-acting antivirals, warrant further consideration in PLWH.
Keywords: antiviral therapy; coinfection; hepatitis B; hepatitis C; hepatitis delta; HIV; Scopus; JCR